Calciphylaxis of the Postmenopausal Female Breast: An Uncommonly Encountered Mimic of Carcinoma. (9th August 2017) - Novotny, Aaron G.; Simpson, Ashley B.; Kral, Melinda A.; Calhoun, Benjamin C.; Cocco, Amy E.; Billings, Steven D.; Miller, Susan K.; Lebda, Paulette L.; Sturgis, Charles D.
Abstract : Calciphylaxis is a serious medical condition that is typically associated with end-stage renal disease and presents as the sequelae of calcifications in arterioles with subsequent ischemia of affected tissues. Classically, calciphylaxis produces ulcerated and necrotic skin lesions. These may be biopsied to aid in confirmation of the diagnosis. Herein we report a case of a large necrotic breast lesion in the clinical setting of calciphylaxis, and we emphasize that a multidisciplinary approach to diagnosis and management is important to avoid unnecessary oncological resection.